Aplikasi Tutorial Resep Masakan Tradisional Aceh Berbasis Android Menggunakan Metode Analytical Hierarchy Process (AHP) - Rozzi Kesuma Dinata (JISKA (Jurnal Informatika Sunan Kalijaga), 2018)
Traditional Aceh cuisine is a dish cooked by the people of Aceh and marinade formulated by the people of Aceh. Based on the results of interviews with the community around the traditional dishes are often cooked every day such as "kuah plik/ patarana, kuah asam keu-eung, kuah masak puteh, kuah lemak/santan, kuah masak mirah, boh manok U, asam sabee, bileh payeh, asam u, dan urap Aceh".  Nowadays according to the advanced application can help the young mothers who from not able to cook become skilful cooking Aceh cuisine, one of them is from the application of traditional recipe of Aceh-based recipe android so that the young mothers can be assisted in the process of way cooking Aceh cuisine. In implementing the AHP method, the authors use the method on the portion of the cuisine divided into 3 (three) portion division of which the three portion, the seven portions and the 12 portions. We show that results in rankings of the most desirable of the 12th share with the highest ranking value of the calculation are 0.37.